Korean Indigenous Knowledge of Health in Korean Drama Jewel in The Palace - Nurislaminingsih, Rizki; Rizal, Edwin; Laksono, Arido (Faculty of Humanities, Diponegoro University, 2024)
Korea is famous for the creative industry such as drama which set in modern times and the kingdom era (saeguk). In the saeguk drama, Korean Indigenous knowledge is also shown. It represents their traditional life, such as livelihoods, how to make tools, survive in four seasons, how to farm or garden, and also about health. One of the saeguk with the theme of Indigenous knowledge is Jewell in the Palace, with the background of the lives of physicians and healers in the Joseon era. This study aims to identify the health themes in the drama text. Therefore, we use qualitative content analysis. The results of the study show that in Jewell in the Palace, there are twelve main themes about health: the relationship between body changes and health, herbs, flowers, acupuncture, healthy drinks, environmental influence on health, benefits of plants for health, spices, fruits, benefits of animals for human health, healthy tips, and natural ingredients for skincare. The conclusion is that the Korean drama Jewell in the Palace has main themes and sub-themes about health based on their characteristics, types of plants, names of animals, and the benefits. The results of this study can be a source of reference for further research from several disciplines: cultural science (cultural and media studies), health (traditional medicine), education (the effectiveness of drama as a source of learning about Indigenous knowledge), and research studies to analyze the use of entertainment media (films, movies, comedy series, and dramas) as sources of research data.